MEK1/2 Inhibitors Unlock the Constrained Interferon Response in Macrophages Through IRF1 Signaling - Yang, Lei; Ding, Jeak Ling (Frontiers in Immunology, 2019)
Macrophages are immune sentinels essential for pathogen recognition and immune defense. Nucleic acid-sensing toll-like receptors like TLR7 activate tailored proinflammatory and interferon responses in macrophages. Here we found that TLR7 activation constrained itself and other TLRs from inducing interferon response genes in macrophages through MAPK kinase 1/2 (MEK1/2)-dependent IRF1 inhibition. Downstream of the MEK1/2-ERK pathway, TLR7-activated macrophages induced interleukin-10 (IL-10), a signal transducer and activator of transcription 3 (STAT3) signaling axis, which constrained the expression of interferon response genes, immunomodulatory cytokines and chemokines. Nevertheless, MEK1/2 inhibitors unlocked an IRF1-interferon signature response in an NF-B-dependent manner. Deficiency in interferon regulatory factor 1 (Irf1) completely abrogated the interferon response and prevented the reprogramming of macrophages into an immunostimulatory phenotype. As a proof of concept, combination treatment with a TLR7 agonist and MEK1/2 inhibitor synergistically extended the survival of wild-type but not Irf1-deficient melanoma-bearing mice. In a retrospective study, higher expression of Irf1 and interferon response genes correlated with more favorable prognosis in patients with cutaneous melanoma. Our findings demonstrated how MEK1/2 inhibitor unlocks IRF1-mediated interferon signature response in macrophages, and the therapeutic potentials of combination therapy with MEK1/2 inhibitor and TLR7 agonist.